Development of subtype-selective covalent ligands for the adenosine A2B receptor by tuning the reactive group. Issue 7 (30th June 2022) - Beerkens, Bert L. H.; Wang, Xuesong; Avgeropoulou, Maria; Adistia, Lisa N.; van Veldhoven, Jacobus P. D.; Jespers, Willem; Liu, Rongfang; Heitman, Laura H.; IJzerman, Adriaan P.; van der Es, Daan
Abstract : Selectivity of covalent ligands for the adenosine A2B receptor was induced by tuning the reactivity and orientation of the warhead. Abstract : Signalling through the adenosine receptors (ARs), in particular through the adenosine A2B receptor (A2B AR), has been shown to play a role in a variety of pathological conditions, ranging from immune disorders to cancer. Covalent ligands for the A2B AR have the potential to irreversibly block the receptor, as well as inhibit all A2B AR-induced signalling pathways. This will allow a thorough investigation of the pathophysiological role of the receptor. In this study, we synthesized and evaluated a set of potential covalent ligands for the A2B AR. The ligands all contain a core scaffold consisting of a substituted xanthine, varying in type and orientation of electrophilic group (warhead). Here, we find that the right combination of these variables is necessary for a high affinity, irreversible mode of binding and selectivity towards the A2B AR. Altogether, this is the case for sulfonyl fluoride 24 (LUF7982), a covalent ligand that allows for novel ways to interrogate the A2B AR.